2014
DOI: 10.4102/ojvr.v81i1.715
|View full text |Cite
|
Sign up to set email alerts
|

Bovine trypanosomosis and its fly vectors in three selected settlement areas of Hawa-Gelan district, western Ethiopia

Abstract: A cross-sectional study aimed at investigating the species diversity of fly vectors and estimating the prevalence of bovine trypanosomosis was carried out from October 2009 to May 2010 in selected settlement areas of the Hawa-Gelan district in the western Wollega zone of Ethiopia. Standard methods of sampling and identification were employed for both entomological and parasitological examination. Three species of the genus Glossina (Glossina pallidipes, Glossina morsitans submorsitans and Glossina fuscipes) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
5
4
2
Order By: Relevance
“…In this study three species of trypanosomes identified were T. congolense (52.10%), T. vivax (32.30%), and T. brucei (10.40%) and mixed infection with T. congolense and T. vivax (5.20%). These species were widespread in most parts of Western and South Western Ethiopia [43,44]. The high proportion of T. congolense (52.10%) in the present study is in agreement with previous reports of [45] at Pawe, North west Ethiopia (60.9%), [46] in selected sites of southern region (63.4%) and [47] in West Gojam (54.3%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study three species of trypanosomes identified were T. congolense (52.10%), T. vivax (32.30%), and T. brucei (10.40%) and mixed infection with T. congolense and T. vivax (5.20%). These species were widespread in most parts of Western and South Western Ethiopia [43,44]. The high proportion of T. congolense (52.10%) in the present study is in agreement with previous reports of [45] at Pawe, North west Ethiopia (60.9%), [46] in selected sites of southern region (63.4%) and [47] in West Gojam (54.3%).…”
Section: Discussionsupporting
confidence: 92%
“…The relative low level of tsetse population in the present study may be due to the control intervention under taken in the area by National Tsetse and Trypanosomosis Investigation and Control Center (NTTICC) and expansion of farmlands leading to the destruction of tsetse habitat and elimination of their wild hosts [69]. A higher number of female tsetse species 366 (54.87%) were caught than male 301(45.13%), and this is in line with reports from the country [56] and [44]. This could be attributed to the longer lifespan of female compared to male Glossina [48].…”
Section: Discussionsupporting
confidence: 89%
“…The current finding was lower than the reports in Southern Ethiopia 14.2% by Feyissa Begna et al (2011) and 27.5% by Abraham Zecharias and Tesfaheywet Zeryehun (2012) and in western Ethiopia 10.8% by Kumela Lelisa et al (2014). This is because of the implementation of different prevention and control measures in the area such as the use of trypanocidal drugs in the form of prophylactic/treatment and the implementation of community based vector control measures (using traps and insecticide impregnated targets).…”
Section: Discussioncontrasting
confidence: 77%
“…Measuring the mean PCV value is one of the indicator of a herd infected with trypanosomosis and hence the anemic status of sampled animals showed reduced PCV values. Such result was also reported by Lelisa et al [25]; Tasew and Duguma [26]; Zecharias and Zeryehun [27]; Kassaye and Tsegaye [28]. Thus, the development of anemia is the most reliable indication of the progress of the trypanosome infection.…”
Section: Citationsupporting
confidence: 80%